An Observational Study on Cosmetics Use-related Adverse Effects: Cosmetovigilance Need of the Day - Mehta, Geetika; Tyagi, Daksh Raj; Sachdeva, Monika; Tripathi, Rashmi; Tyagi, Himanshu (Drug Research, 2024)
Introduction The pursuit of aesthetic attractiveness and increased awareness have contributed significantly to the growth of the cosmetic industry. However, it is crucial to recognize that even the minimal use of cosmetics may have harmful consequences for both the overall well-being and the broader community, an issue that has yet to be adequately recognized or addressed.Objective This study is aimed at providing insights into the usage pattern of consumer behavior regarding skin care products and to assess the prevalence and determinants of cosmetic-related adverse events among the general populace.Materials and Methods A community-based cross-sectional study was carried out for four months in a satellite city of the National Capital Region (NCR) of India. The data from 435 respondents was collected using a self-administered questionnaire and analyzed using frequencies and percentages.Results Among 435 participants, 32.9% experienced one or more adverse effects owing to the use of skincare products; the prevalence was higher in females (36.3%). Hair loss, allergies, and dry skin were the most frequently reported adverse effects. The majority of the adverse reactions were reported with soap (21%), followed by shampoo (17%). The gender-wise difference between adverse effects of skin care products was found to be statistically significant.Conclusion To improve the system’s efficiency, a comprehensive review of the current regulatory protocols for cosmetics is crucial. Additionally, it is essential to widely disseminate information on Cosmetovigilance and promote the reporting of any adverse effects of cosmetics within the community; this is the demand of the present time.
Keywords: cosmetics; adverse effects; cosmetovigilance; utilization behavior